Development and validation of a nomogram for suicide attempts in patients with first-episode drug-naïve major depressive disorder - Liu, Junjun; Tong, Ruixiang; Lu, Zhaomin; Wang, Zhiye; Wang, Yangchun; Liu, Yang; Yuan, Hsinsung; Jia, Fengnan; Zhang, Xiaobin; Li, Zhe; Du, Xiangdong; Zhang, Xiangyang (Frontiers in Psychiatry, 2024)
Abstract Objective: The risk of suicide can be decreased by accurately identifying high-risk suicide groups and implementing the right interventions. The aim of this study was to develop a nomogram for suicide attempts (SA) in patients with first-episode drug-naïve (FEDN) major depressive disorder (MDD). Methods: This study undertook a cross-sectional analysis of 1,718 patients diagnosed with FEDN MDD, providing comprehensive clinical data from September 2016 to December 2018. Data on anthropometric and sociodemographic factors were gathered, and the severity of depression and anxiety was evaluated using the HAMD-17 and the HAMA, respectively. Additionally, thyroid hormone levels, lipid profile parameters, and FBG were measured. Suicide attempt (SA) history was verified based on an amalgamation of medical records, patient interviews, and family interviews. Participants were randomly divided into a training group (70%, n = 1,204) and a validation group (30%, n = 514). In the training group, LASSO analysis and multivariate regression were used to identify variables associated with SA. A nomogram was then constructed using the identified risk factors to estimate the likelihood of SA within the training group. To assess the accuracy, the AUC was utilized, and calibration plots were employed to evaluate calibration. Additionally, DCA was performed to assess the precision of the model. Finally, internal validation was carried out using the validation group. Results: A practical nomogram has been successfully constructed, incorporating HAMD, HAMA, TSH, TPOAb, and SBP parameters, to estimate the probability of SA in Chinese patients diagnosed with FEDN MDD. The pooled area under the ROC for SA risk in both the training and validation groups was found to be 0.802 and 0.821, respectively. Calibration analysis revealed a satisfactory correlation between the nomogram probabilities and the actual observed probabilities. The clinical applicability of the nomogram was confirmed through decision curve analysis. To enhance accessibility for clinicians and researchers, an online version of the nomogram can be accessed at https://doctorjunjunliu.shinyapps.io/dynnomapp/. Conclusions: We constructed and validated a nomogram for the early detection of FEDN MDD patients with a high risk of SA, thereby contributing to the implementation of effective suicide prevention programs.